Mode switching analysis and control for a parallel hydraulic hybrid vehicle. Issue 6 (3rd June 2021) - Zhou, Shilei; Walker, Paul; Tian, Yang; Zhang, Nong
Abstract : Parallel hydraulic hybrid vehicles (PHHVs) integrate conventional engines with a hydraulic pump/motor (HPM) to drive the vehicle independently or in combination. To improve the comfortability and drivability during mode switching from hydraulic driving mode to engine driving mode, this paper proposes a coordinated control strategy for the engine, clutch and HPM. To capture the transient behaviour of the powertrain, a medium-duty PHHV dynamic model is established. Based on a typical PHHV powertrain layout, the mode switching process is analysed and divided into five phases. Control strategies are designed for each phase, respectively.LQR-based closed-loop control strategy is adopted to analyse the effect of clutch engaging speed on vehicle jerk, clutch frictional work and energy consumption. HPM output torque is adjusted to compensate the engine clutch drag torque, with the aim maintaining good drivability. To do this, constant vehicle acceleration is selected as the indicator of stable output torque. The simulation results demonstrate that by using the HPM to compensate the engine clutch drag torque, vehicle drivability is guaranteed during mode switching. From the comparison between different LQR weighting matrices, multiple options are available to drivers on drivability and comfortability during mode switching.